Copper‐Chelating Azides for Efficient Click Conjugation Reactions in Complex Media1. (30th April 2014) - Bevilacqua, Valentina; King, Mathias; Chaumontet, Manon; Nothisen, Marc; Gabillet, Sandra; Buisson, David; Puente, Céline; Wagner, Alain; Taran, Frédéric
Abstract The concept of chelation‐assisted copper catalysis was employed for the development of new azides that display unprecedented reactivity in the copper(I)‐catalyzed azide–alkyne [3+2] cycloaddition (CuAAC) reaction. Azides that bear strong copper‐chelating moieties were synthesized; these functional groups allow the formation of azide copper complexes that react almost instantaneously with alkynes under diluted conditions. Efficient ligation occurred at low concentration and in complex media with only one equivalent of copper, which improves the biocompatibility of the CuAAC reaction. Furthermore, such a click reaction allowed the localization of a bioactive compound inside living cells by fluorescence measurements.